PENERAPAN TEKNOLOGI QR CODE PADA SISTEM ABSENSI DI KLINIK ADIANDRA - Taryanto, Ardi; Listianti, Yulia; Alim, Agus; Sastradipraja, Cecep Kurnia; Hamdani, Aldi (POLITEKNIK PIKSI GANESHA, 2025)
Adiandra Medika Clinic is a healthcare facility that still uses a manual method for recording employee attendance. This approach leads to several issues, such as inaccurate records, data manipulation, slow recap processes, and paper waste. This study aims to design a digital attendance system using QR Code to record attendance more accurately and efficiently. Data were collected through on-site observation and interviews. The system was developed using the Waterfall model, designed with UML, and built using the CodeIgniter framework in a web-based environment. Testing was conducted using the black box method to ensure all features function as required. The results show that the system improves the speed of attendance recording, minimizes errors, and supports real-time monitoring. The system is feasible for implementation and can be adopted by clinics or similar institutions in need of a digital attendance solution. Its implementation is also expected to enhance the overall management of human resources.